Characterization of nutritional, organoleptic and functional properties of intermediate moisture shelf stable ready-to-eat Carica papaya cubes. (1st June 2015) - Mishra, Bibhuti Bhusan; Gautam, Satyendra; Chander, Ramesh; Sharma, Arun
Abstract: Papaya fruit is highly perishable resulting in around 25% postharvest losses which is further enhanced during storage and transportation. To prevent these losses intermediate moisture (IM) papaya cubes were developed using a novel combination technology including osmotic dehydration, blanching and infrared drying. These cubes were further hygienized by exposing to gamma radiation dose of 2 kGy. The final processed product could be stored up to 60 days at ambient temperature, whereas, the unprocessed freshly cut samples spoiled within 2 days. Nutritional analysis of IM cubes indicated nearly 5 fold increase in calorie value with significant increase in the per unit dry weight content of carbohydrate, protein, fibre, and functional bioactives such as ascorbic acid, carotenoids, and phenolics including flavonoids. The activity of oxidising enzymes, polyphenol oxidase and peroxidase, was reduced by 88 and 96%, respectively in IM papaya cubes. The functional properties in terms of antioxidant capacity and antimutagenic potential were improved. The processing ensured the microbiological safety of the product. Organoleptically the product was found to be well acceptable by the taste panellists. The findings thus could help reduce postharvest losses in papaya by providing a technology to make ready-to-eat (RTE) nutrient rich product.